Study Compatibility Conceptual Design of Modular House Wall Panel by Using Solidwork - Zadeli, Mohd Zuhdi Hidayat; MUSTAFA, MOHAMMAD SUKRI; Mohd Rasidi Ibrahim (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study dives into how well different designs for modular house wall panels fit together, using SolidWorks to create the designs and ANSYS to give them a thorough check-up. While modular construction is great for being efficient and eco-friendly, making sure all the parts work seamlessly can be tricky. With SolidWorks, a user-friendly CAD tool, we craft detailed designs for these wall panels, keeping an eye on things like strength, material use, and how easy they are to put together. Then, we turn to ANSYS to test the panels under different kinds of stress, seeing how they hold up and where they might need some tweaking. By combining these tools, we hope to make modular construction systems even better, helping to make buildings more sustainable and easier to build.